-2x-28=67-7x

Simple and best practice solution for -2x-28=67-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-28=67-7x equation:


Simplifying
-2x + -28 = 67 + -7x

Reorder the terms:
-28 + -2x = 67 + -7x

Solving
-28 + -2x = 67 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-28 + -2x + 7x = 67 + -7x + 7x

Combine like terms: -2x + 7x = 5x
-28 + 5x = 67 + -7x + 7x

Combine like terms: -7x + 7x = 0
-28 + 5x = 67 + 0
-28 + 5x = 67

Add '28' to each side of the equation.
-28 + 28 + 5x = 67 + 28

Combine like terms: -28 + 28 = 0
0 + 5x = 67 + 28
5x = 67 + 28

Combine like terms: 67 + 28 = 95
5x = 95

Divide each side by '5'.
x = 19

Simplifying
x = 19

See similar equations:

| (5a-3)(5a-3)= | | 2x/x-9-x/2(x-9)= | | 3(2x-5)-(x+3)=(2x+1)+4 | | 7=10-3u | | 5a-2=3a+4 | | 2(x-4)+12=x-4(6+2x)+9x | | 12×-1/3 | | 13=10 | | 3log(2)x=28 | | -53/4-31/2= | | 4x-40=13-6x+3 | | 2y-10x=10 | | 3.50x=10.50 | | 3x^2+10=100 | | 2x+7=15+4x | | 2x+12+9=x+3 | | 6x+5+9x-10+80+90=360 | | X+6=-8x+5 | | (x^2+0.8)(x^2+0.8)= | | 3x-29=17-5x | | 18=9+3h | | 7tanx+2=9 | | 3y+6-2=8-2y | | 7/3*8/6 | | -4/7y16 | | 12=15-3p | | 2(x-4)+12=x-4(6+2x)+9 | | 42r^2-35r=0 | | -5+1y=-8x | | 15=2v+3 | | 9p-4q=-15 | | 8=10-2r |

Equations solver categories